Synchronous Pulmonary Squamous Cell Carcinoma and Mantle Cell Lymphoma of the Lymph Node - Yu Sun; Yun-Fei Shi; Li-Xin Zhou; Ke-Neng Chen; Xiang-Hong Li (Case Reports in Genetics)
Synchronous occurrence of pulmonary squamous cell carcinoma and malignant lymphoma of the lymph node is not reported in the literature. We report a case of pulmonary squamous cell carcinoma coexisting with a mantle cell lymphoma involving cervical and mediastinal lymph node. It is important to recognize this synchronous occurrence histopathologically and to be aware of the existence of “in situ” MCL.